Analiza zvočnih lastnosti kompozitnih materialov - Šali, Samo (Strojniški vestnik, 2004)
To help select the best material for loudspeaker boxes, we tested various types of polymer materials that are filled with fine, ground wood particles. In addition, we compared these materials with aluminium, MDF (medium-density fiberboard), polystyrene from another producer of loudspeaker boxes (JVC), andABS (acrylnitril - butadiene - styrene). All the specimens were in the shape of square plates with dimensions 150 150 mm and the thickness 2 mm. Because the analysis was focused on the acoustic properties of the materials, we measured their relative sound-wave resistance, the relative damping of the sound radiation and the viscous-damping factor. The first two parameters are derived from the density and the relative modulus of elasticity, which can be obtained from measurements of the frequency response for free-supported specimens. The results show that a careful selection of fine, ground wood particles and polymer can give a satisfactory approximation to MDF, which is known as one of the best choices for the production of loudspeaker boxes.
Keywords: materiali kompozitni; lastnosti akustične; analize modalne; metode preskušanja; kompoziti; zvočne lastnosti; ohišja